Quercetin reverses β1-adrenoceptor autoantibody-induced heart failure by promoting MDM2-mediated ubiquitination and degradation of p53 in cardiomyocytes - Ma, Mingxia; Jiang, Xintai; Liu, Weiqian; Xue, Jin; Yuan, Yuan; Zhi, Xiaoyan; Feng, Jiayan; Long, Yaolin; Li, Yang; Zhang, Zhijun; Wang, Xiaohui; Wang, Li (Frontiers in Nutrition, 2025)
IntroductionCardiomyocyte autophagy is essential for preserving cardiac homeostasis. Previous studies revealed that β1-adrenergic receptor autoantibody (β1-AA) suppressed cardiomyocyte autophagy, triggering cell death and heart failure (HF). Qiliqiangxin capsule enhances autophagy and mitigates HF through multiple pathways, but its complex composition complicates mechanistic clarity. Network pharmacology identified quercetin as a pivotal autophagy-inducing component in Qiliqiangxin, yet its role in counteracting β1-AA-induced autophagy impairment remains unvalidated. In this study, quercetin’s therapeutic potential and mechanisms in restoring autophagy in β1-AA-associated HF were investigated.MethodsBioinformatics methods, including a STRING database analysis, PPI network construction, and Cytoscape-based pathway mapping, were used to delineate quercetin’s autophagy-related targets. The in vivo efficacy was assessed in β1-AA-positive mice treated with quercetin (100 mg/[kg·d], intraperitoneal). The in vitro validation used H9c2 cardiomyocytes pretreated with quercetin (100 μM) prior to β1-AA exposure. Autophagy markers, p53 signaling, and ubiquitination pathways were analyzed by immunoblotting and functional enrichment analysis using the GOrilla database. A p53 knockdown and overexpressing cardiomyocyte model confirmed pathway specificity.ResultsQuercetin administration significantly restored myocardial autophagy levels in β1-AA-positive mice, which improved cardiac function and survival rates. In H9c2 cells, quercetin pretreatment reversed β1-AA-induced autophagy suppression. Bioinformatics linked quercetin to p53 pathway modulation, with experimental validation showing quercetin downregulated p53 expression via MDM2-mediated ubiquitination. p53 knockdown enhanced autophagy, while its overexpression blocked quercetin’s effect, indicating quercetin restores autophagy in a p53-dependent manner. GO enrichment highlighted the association between quercetin and ubiquitin-dependent protein degradation, which was corroborated by elevated MDM2 levels and accelerated p53 degradation in quercetin-treated cells.DiscussionQuercetin rescues β1-AA-impaired cardiomyocyte autophagy by activating MDM2-dependent p53 ubiquitination and degradation, thereby attenuating HF progression. These findings establish quercetin as the mechanistic basis of the cardioprotective effects of Qiliqiangxin and provide preclinical evidence for targeting autophagy by regulating p53 in β1-AA-induced cardiac dysfunction.